Alzheimer's disease is associated with altered expression of genes involved in immune response and mitochondrial processes in astrocytes - Sekar, Shobana; McDonald, Jacquelyn; Cuyugan, Lori; Aldrich, Jessica; Kurdoglu, Ahmet; Adkins, Jonathan; Serrano, Geidy; Beach, Thomas G.; Craig, David W.; Valla, Jonathan; Reiman, Eric M.; Liang, Winnie S. (Neurobiology of aging, 2015)
Alzheimer's disease (AD) is characterized by deficits in cerebral metabolic rates of glucose in the posterior cingulate (PC) and precuneus in AD subjects, and in APOEε4 carriers, decades before the onset of measureable cognitive deficits. However, the cellular and molecular basis of this phenotype remains to be clarified. Given the roles of astrocytes in energy storage and brain immunity, we sought to characterize the transcriptome of AD PC astrocytes. Cells were laser capture microdissected from AD (n = 10) and healthy elderly control (n = 10) subjects for RNA sequencing. We generated >5.22 billion reads and compared sequencing data between controls and AD patients. We identified differentially expressed mitochondria-related genes including TRMT61B, FASTKD2, and NDUFA4L2, and using pathway and weighted gene coexpression analyses, we identified differentially expressed immune response genes. A number of these genes, including CLU, C3, and CD74, have been implicated in beta amyloid generation or clearance. These data provide key insights into astrocyte-specific contributions to AD, and we present this data set as a publicly available resource.